2003
DOI: 10.1110/ps.0302503
|View full text |Cite
|
Sign up to set email alerts
|

Contact order revisited: Influence of protein size on the folding rate

Abstract: Guided by the recent success of empirical model predicting the folding rates of small two-state folding proteins from the relative contact order (CO) of their native structures, by a theoretical model of protein folding that predicts that logarithm of the folding rate decreases with the protein chain length L as L 2/3 , and by the finding that the folding rates of multistate folding proteins strongly correlate with their sizes and have very bad correlation with CO, we reexamined the dependence of folding rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
397
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(430 citation statements)
references
References 64 publications
30
397
0
3
Order By: Relevance
“…Much work on the folding rate prediction was published in the pureempirical approach. They include the prediction model based on amino acid sequence [18,2628], based on tertiary structure [15,29] and based on secondary structure [17], etc. The prediction accuracy is generally dependent on the size of database.…”
Section: Results Of Statistical Analysis Of 65 Two-state Protein Foldmentioning
confidence: 99%
See 1 more Smart Citation
“…Much work on the folding rate prediction was published in the pureempirical approach. They include the prediction model based on amino acid sequence [18,2628], based on tertiary structure [15,29] and based on secondary structure [17], etc. The prediction accuracy is generally dependent on the size of database.…”
Section: Results Of Statistical Analysis Of 65 Two-state Protein Foldmentioning
confidence: 99%
“…(10) then the prediction accuracy on folding rate from (1) and (11) will be further increased, the correlation coefficient R between theoretical and experimental logarithm rate for 65 two-state proteins attained 0.78 [57]. [15] and ACO [29] from web server at http://depts.washington.edu/bakerpg/contact_order/. f) Size-modified contact order SMCO=RCO×L 0.7 [29], L, number of residues that have defined three-dimensional coordinates and contribute to the relative contact order (RCO) calculations.…”
Section: Results Of Statistical Analysis Of 65 Two-state Protein Foldmentioning
confidence: 99%
“…The observation that low "contact order", which implies a high ratio of LIs to NLIs in the folded structures of proteins, is correlated with high rate of folding seems to give strong support to the role of LIs in determining the folding rate (Plaxco et al 1998;Ivankov et al 2003). Weikl (Weikl and Dill 2003;Weikl 2008) introduced the concept of effective contact order and showed that closure of small loops shows improved correlation with the global folding rate.…”
Section: O'neill Et Al (O'neill and Robert Matthews 2000)mentioning
confidence: 98%
“…One important insight from experimental studies is that for many proteins the rate of folding is inversely correlated to the density of sequence-distant contacts (referred to as "contact order") in the native state [3,15]. This correlation suggests that the overall fold or "topology" of the native-state is established in the rate-limiting step in folding [16].…”
Section: Recent Observations and Related Questions In Folding Of Globmentioning
confidence: 99%